The Individual Investor's Microcomputer Resource Guide / A Publication of the American Association of Individual Investors (International Publishing Corporation, 1987)
The Guide describes the latest investment software, hardware, books and financial information services available for the individual investor. Preface, An Introduction to Computer-Aided Investing, Microcomputer Hardware, Selecting Investment Software and Financial Databases, Guide to Investment Software, Gide to Financial Databases, Suggested Readings, Index of Investment Software and Financial Data Services.